2010
DOI: 10.1002/ffj.1998
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles from Plicanthus hirtellus (F. Weber) R.M. Schust. and Radula boryana (F. Weber) Nees (Hepaticae) grown in São Tomé e Príncipe Archipelago

Abstract: ABSTRACT:The main goal of this study was to isolate and characterize the volatiles from Plicanthus hirtellus and Radula boryana grown in the African Archipelago of São Tomé e Príncipe. The volatiles isolated by distillation-extraction from Plicanthus hirtellus and Radula boryana were analysed by GC and GC-MS. Plicanthus hirtellus volatiles were dominated by anastreptene (13%) and spathulenol (14%). Radula boryana volatiles were characterized by high amounts of p-cymene (17%) along with other monoterpene hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…A fraction designated by others, which was mainly composed of non-aromatic alcohols, non-aromatic aldehydes, hydrocarbons, and fatty acids (1 -31%), reached also, in some cases, The percentage composition of the oils was computed by the normalization method from the GC peak areas, calculated as mean values of two injections from each oil, using the response factors as detailed in [26]. A fraction designated by others, which was mainly composed of non-aromatic alcohols, non-aromatic aldehydes, hydrocarbons, and fatty acids (1 -31%), reached also, in some cases, The percentage composition of the oils was computed by the normalization method from the GC peak areas, calculated as mean values of two injections from each oil, using the response factors as detailed in [26].…”
mentioning
confidence: 99%
“…A fraction designated by others, which was mainly composed of non-aromatic alcohols, non-aromatic aldehydes, hydrocarbons, and fatty acids (1 -31%), reached also, in some cases, The percentage composition of the oils was computed by the normalization method from the GC peak areas, calculated as mean values of two injections from each oil, using the response factors as detailed in [26]. A fraction designated by others, which was mainly composed of non-aromatic alcohols, non-aromatic aldehydes, hydrocarbons, and fatty acids (1 -31%), reached also, in some cases, The percentage composition of the oils was computed by the normalization method from the GC peak areas, calculated as mean values of two injections from each oil, using the response factors as detailed in [26].…”
mentioning
confidence: 99%
“…Two other characteristic components were thymol (50) and carvacrol (51) (Figure 4). [51] This study indicated chemotaxonomical value for the EO composition of Radula species.…”
Section: Leafy Liverwortsmentioning
confidence: 59%
“…A survey of the scientific literature revealed more papers concerning EOs obtained from the Marchantiophyta. These data concern the chemical composition of EOs from such liverwort species as Barbilophozia floerkei, [65] Calypogeia muelleriana, [72] Chandonanthus hirtellus (=Plicanthus hirtellus), [51] Scapania undulata, [73] and Tritomaria polita, [74] among others. However, it is difficult to draw chemotaxonomic conclusions from a single type of data.…”
Section: Leafy Liverwortsmentioning
confidence: 99%
“…The volume of injection was 0.1 µl of a pentane–volatiles solution (1:1). The percentage composition of the essential oils was computed by the normalization method from the GC peak areas, calculated as mean values of two injections from each sample, using response factors as detailed in Figueiredo et al …”
Section: Methodsmentioning
confidence: 99%